Numerical Analysis of a Small Pneumatic Hammer Performance Based on Evaluation Method of Friction Force - Un Hyok Yang; Tok Hyong Han; Un Chol Han; Il Gwang Tae; Ryo Myong Hong; Song Chol Kim (Shock and Vibration)
Mechanical power loss in pneumatic hammers comes from the friction between parts in relative motion, and wear is among the failure mechanisms of the top hammer. Therefore, it is important for high performance and a longer service life of pneumatic hammers to reduce the friction force between parts in relative motion. This study presented a novel approach to quantitatively determine the friction force and consider it in the simulation model of pneumatic hammer. First, the friction force between piston and cylinder in a small pneumatic hammer was measured using an experimental setup at different inlet pressures. We could find from the experimental result that the friction force was about 0.8 N under the horizontal installation when there was no pressure supply, but it increased significantly, was 20 times greater than that without pressure supply, due to aerodynamic action by compressed air leaked from the annular gaps between the cylindrical matching surfaces of the components. In addition, it increased from 10.27 to 16.7 N due to an increase in inlet pressure and mechanical power loss in the pneumatic hammer that was about 10% of impact energy. Then, numerical analysis for a small pneumatic hammer performance was performed by a model considered the friction force using AMESim software. Finally, it can be seen from the simulation results that the proposed approach could significantly reduce the error between the simulated and the measured values for the impact energy because of ignoring the friction force. This approach will be used to predict service life of piston and find a low friction piston of pneumatic hammer in practical engineering.